THE ORIES ON LISTENING COMPREHENSION IN LANGUAGE LEARNING - Utepbergenova, D.; Kurbaniyazova, S. (FAN va JAMIYAT, 2020)
The article deals with one of the most important components of oral speech communication as listening comprehension. The authors endeavor to review several important listening comprehension theories and figure out their significance in teaching listening. It reviews the importance of listening in language comprehension, the psychological processes of listening and the intended communicative outcomes of listening.